Basis for the geological heritage management in the Azores Archipelago (Portugal) - Lima,Eva Almeida (2014)
The Azores archipelago, with a peculiar geodynamic setting, presents a huge geodiversity and important geological heritage, being considered a natural laboratory of volcanic geodiversity. In the last decade, the geodiversity and geological heritage of the Azores archipelago is being inventoried, characterized, quantified, protected and promoted. Nowadays there are identified and characterized 121 geosites distributed through the nine islands and the surrounding seafloor. These geosites network ensure the representativeness of the Azorean geodiversity and reflects its geological and eruptive history with about 10 million years. Among the geosites, 57 were selected as priorities for the development of geoconservation strategies and implementation of promotion actions. The analysis of the geosites included two main phases: a qualitative and a quantitative assessment, integrating the geological characterization, geomorphological and volcanological categorization, analysis of their relevance, identification of the potential type of use in each geosite, its scientific value and other associated values. The efforts resulted recognition of 6 geosites with international relevance [e.g. the Mid Atlantic Ridge, the Caldera of Furnas volcano (São Miguel island), the Pico Mountain (Pico island), the Caldera and Furna do Enxofre (Graciosa island), the Capelinhos volcano and Costado da Nau (Faial island) and Algar do Carvão volcanic pit (Terceira island)] and 52 geosites of national relevance. Besides its scientific value, most of the geosites have a relevant educational and geotouristic value. It is noteworthy that 93 geosites integrate the Regional Network of Protected Areas, lying under the management of the Island Natural Parks and the Marine Park. The volcanic landscapes of the Azores have been promoted since the late twentieth century, especially for tourism campaigns, however since the begining of the work studies of the geological heritage of the archipelago in 2007, has also been promoted regionally, nationally and internationally.